Electrochemical degradation of PAHs in produced water using Ti/Sb2O5-SnO2-IrO2 anode - Yaqub, A. (Electrochemical Society of Japan, 2014)
In the study, ternary oxides coated Ti/SnO2-Sb2O5-IrO2 anode was used for degradation of 16 priority polycyclic aromatic hydrocarbons (PAHs) in a laboratory scale electrochemical batch reactor. To determine the optimum conditions for electrochemical degradation of PAHs from produced water, Box-Behnken design was used with three independent variables, viz., current density, pH and electrolysis time and response variable, viz., Î£PAHs removal. Quadratic regression model was recommended as the best fit model. The results of Analysis of Variances (ANOVA) exhibited that the regression model adequately described the functional relationship between the independent variables and the response. This study affirmed that electrochemical degradation of PAHs followed first-order kinetics. Â©2014 The Electrochemical Society of Japan, All rights reserved.